The role of PPAR ligands in collecting duct growth and apoptosis - Clark, Jordan (University of Ottawa (Canada), 2008)
The collecting duct (CD) has considerable expression of PPARdelta and PPARgamma. While their roles are unknown in the CD, in other cells they have been shown to regulate both growth and apoptosis. We thus investigated the hypothesis that PPARs reduce apoptotic responses in the mouse collecting duct IMCD-K2 and M-1 cells and that while PPARgamma has an inhibitory effect on cell growth, PPARdelta stimulates growth in these cells. This study characterized the growth and apoptotic responses in the collecting duct cells, M-1 and IMCD-K2, in response to the PPARdelta and PPARgamma ligands, GW501516 and troglitazone. The extent of apoptosis in IMCD-K2 and M-1 cells, induced by anisomycin, was only affected by troglitazone, which reduced the protein levels of cleaved caspase-3 in M-1 cells. GW501516 treatment increased DNA synthesis in IMCD-K2 cells, decreased DNA synthesis in M-1 cells, and decreased protein synthesis in both IMCD-K2 and M-1 cells. Additionally, troglitazone reduced DNA and protein synthesis in M-1 cells, and this effect was unaltered in the presence of the PPARgamma antagonist and ERK inhibitor. However, troglitazone treatment alone increased the levels of pERK. These results show PPAR ligands negatively regulate growth and apoptosis in CD cell lines, but more work is needed to ascertain the therapeutic potential of PPAR ligands in the prevention of CD injury.
Keywords: Biology, Molecular.; Biology, Cell.